Effector mechanisms of influenza-specific antibodies: neutralization and beyond - Federica Sicca; Sam Neppelenbroek; Anke Huckriede (Taylor & Francis Group, 2018)
Introduction: Antibodies directed against influenza virus execute their protective function by exploiting a variety of effector mechanisms. Neutralizing antibodies have been thoroughly studied because of their pivotal role in preventing influenza virus infection and their presence in host serum is correlated with protection. Influenza antibodies can also exploit non-neutralizing effector mechanisms, which until recently have been largely overlooked. Areas covered: Here, we discuss the antibody response to influenza virus in its entire breadth. Neutralizing antibodies mostly target variable epitopes on influenza surface proteins and interfere with virus binding, fusion, or egress. Non-neutralizing antibodies instead usually target conserved epitopes which can be located on surface as well as internal proteins. They drive viral clearance via interaction of their Fc region with components of the innate immune system such as immune effector cells (e.g. NK cells, macrophages) or the complement system. Expert commentary: Recent research has unraveled that influenza-specific antibodies target multiple proteins and make use of diverse effector mechanisms. Often these antibodies are cross-reactive among virus strains of the same subtype or even between subtypes. As such they are induced early in life and are boosted by regular encounters with virus or vaccine. Designing strategies to optimally exploit these pre-existing antibodies may represent the key for the development of new broadly protective influenza vaccines.